Horror, Witches, and Feminism in American Popular Culture: An Intertextual Analysis of TV Series Agatha All Along (Disney+, 2024) - Higueras-Ruiz, María-José; Pérez-Rufí, José-Patricio (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2026)
In the contemporary television industry, fiction series must compete in a saturated market with attractive and innovative proposals. The Marvel universe series Agatha All Along (Disney+, 2025) is a prime example of this scenario due to its metatelevision component. The aim of this study is to determine the intertextual references of this fiction from a feminist and queer perspective. Using a qualitative methodology, a textual analysis of the series is applied to identify and classify these elements. The results show numerous references to the audiovisual medium, with allusions to films and series in the fantasy and horror genres, as well as to the Marvel universe itself, but especially to other elements of popular culture and witches. The series demonstrates a motivation to move away from superheroes and includes diverse women and queer characters who, through popular culture, offers a feminist vision of the figure of the witch.
Keywords: intertextuality; popular culture; feminism; witches; Marvel; TV series